The COVID-19 pandemic increased the demand for pneumococcal vaccination in Japan - Akira Komori; Hirotake Mori; Toshio Naito (Taylor & Francis Group, 2021)
Although routine vaccinations in children decreased during the coronavirus disease 2019 (COVID-19) pandemic, pneumococcal vaccine coverage in older adults has remained unknown. This study was performed to investigate the impact of the COVID-19 pandemic on pneumococcal vaccination in Japan. The numbers of 23-valent pneumococcal polysaccharide vaccines (PPV23) shipped was obtained from an office memorandum released by the Ministry of Health, Labor and Welfare. The results showed that the COVID-19 pandemic increased the need for pneumococcal vaccination, causing shipping restrictions of pneumococcal vaccines. Regular vaccination is still important because there may be a shortage of vaccines during a pandemic.